2021
DOI: 10.1038/s41467-020-20877-8
|View full text |Cite|
|
Sign up to set email alerts
|

Rare genetic variants affecting urine metabolite levels link population variation to inborn errors of metabolism

Abstract: Metabolite levels in urine may provide insights into genetic mechanisms shaping their related pathways. We therefore investigate the cumulative contribution of rare, exonic genetic variants on urine levels of 1487 metabolites and 53,714 metabolite ratios among 4864 GCKD study participants. Here we report the detection of 128 significant associations involving 30 unique genes, 16 of which are known to underlie inborn errors of metabolism. The 30 genes are strongly enriched for shared expression in liver and kid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 81 publications
1
22
0
Order By: Relevance
“…The COBRA approach has been successfully applied to a variety of biomedical questions [17] , [18] , including host-pathogen interactions [19] . One of the advantages of metabolic reconstructions is that they can be tailored to a particular question or condition through the application of constraints [15] , which could, for example, be dietary availability [20] , [21] , [22] , gene defects [23] , [24] , or omics data [25] , [26] , [27] . Hence, one metabolic reconstruction can give rise to many condition-specific models.…”
Section: Introductionmentioning
confidence: 99%
“…The COBRA approach has been successfully applied to a variety of biomedical questions [17] , [18] , including host-pathogen interactions [19] . One of the advantages of metabolic reconstructions is that they can be tailored to a particular question or condition through the application of constraints [15] , which could, for example, be dietary availability [20] , [21] , [22] , gene defects [23] , [24] , or omics data [25] , [26] , [27] . Hence, one metabolic reconstruction can give rise to many condition-specific models.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, genome-wide association studies of urinary metabolites have identified the association between common sequence variants within or close to the genes encoding enzymes and transport proteins that enrich the mitochondrial matrix—the subcellular compartment in which many detoxification reactions and fatty acid and amino acid metabolism occur—and kidney-related traits (i.e. urine albumin-to-creatinine ratio and estimated glomerular filtration rate [ 13 ]) or different disease states, including chronic kidney disease [ 14 ]. These large-scale and multi-omics approaches thus support the fundamental role of mitochondria in organizing cellular homeostasis and organismal physiology, and its contribution to disease risk within the population.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 4,879 GCKD participants with complete data on genotyping (Exome chip), eGFR, UACR and log 2 (OPN) measurements were included in the analysis of aggregated rare variant testing ( S1 Fig ) . As previously described [ 106 ], two types of rare variant aggregation tests (burden test, sequence kernel association test [SKAT]) implemented in the R package seqMeta (v1.6.7, [ 107 ]) were conducted using exome chip data and log 2 (OPN) measurements (outcome). Per gene, variants with MAF <1% and having a major effect on the gene product (nonsynonymous, stop gain/loss, splicing; “qualifying variants”) as annotated by dbNSFP v.2.0 were aggregated [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%